Análisis del impacto de las recaudaciones tributarias producto de las exportaciones de rosas, en el caso Expoflores, Período 2010 -2014 y la salida del Ecuador del ATPDEA - García Muñoz, Carlos Bayardo (2016)
This research aims to analyze the impact of exports rose in Expoflores case and the output of the APTDEA Ecuador in tax revenues from income tax in the period 2010-2014, using deductive, descriptive methodology and Using quantitative survey with a sample of growers, being most important results that exports were growing roses during the years 2011, 2012 and 2013, both in tonnes and in FOB dollars, growing these latest figures on 3.96% in 2012 and 9.23% in 2013, however, a decrease of exports of this well in 2014, both in tonnes (4.24%) and FOB (-0.84%) was observed dollars , after breaking the ATPDEA with the United States, growth of 13%, 25% and 17% in revenues from exports of roses were observed during the years 2011, 2012 and 2013, respectively, with a fall in 2014 equal 5%; like the IR 11.44%, 19.86% and 17% increase in the period 2011, 2012 and 2013, respectively, also falling by 5 percentage points in 2014, which influenced this branch of the economy participate with the lowest percentage (0.35% to 0.29% from 2010 to 2014) in the ranking of the proceeds from all sectors of the economy, meaning that the output of the APTDEA Ecuador, caused the decrease the Ecuadorian roses in the international market and tax revenues, since 2014, government decision which had a negative impact in the flower industry, however, the strategy of the tax bonus, something he is filling the need for growers to remedy this impact and the productive sector to grow in the future.